Kemampuan Mengatasi Masalah Matematis dan Meningkatkan Keyakinan Diri sengan Model Pembelajaran Blended Berbasis Sevima Edlink - Suri, Indah Resti Ayuni; Netriwati; Wulandari, Irma (Journal of Mathematics Education and Science, 2025)
Mathematical problem solving skills make it difficult for students to solve problem solving problems. Low self-confidence is one of the factors that cause students to fail in math. This is because students are not used to solving different mathematical problems because the teaching models used are not varied. The purpose of this study is to find out whether students have the ability to solve mathematical problems and improve their self-confidence as a result of Edlink's Sevima-based blended learning approach. This quasy study used a non-equivalent post-test only control group design. all VIII grade students at MTs N 03 OKU Selatan. The cluster random sampling method was used to take the sample. Mathematical problem solving ability test and student confidence questionnaire were used in this study. The normality test yields the sig. value = 0.899 > 0.05 and sig. value = 0.962 > 0.05 if the students' self-esteem data are normally distributed. For the homogeneity test, the sig. 0.05 is 0.583 with data from both classes is homogeneous. In the multicollinearity test, the Tolerance value of 0.912 is greater than 0.1 and the VIF value of 1.097 is less than 10, with the research data having no multicollinear correlation. The results of the study, conducted with Manova Test, showed that students who received Edlink's Sevima-based blended learning had better math problem-solving skills and improved confidence than students who received direct instruction.